Hello, imthatgirl!

Can anyone explain how to solve this?

There's 3 equations and 3 variables, but only 2 variables in each equation.

. . 2a - 5c .= .-18

. . 7b - 8c .= .-65

. . 3a - 2b .= . 2

Missing variables should not be a problem.

If you're using Elimination, they actually did us a favor! Code:

(1) 2a - 5c = -18
(2) 7b - 8c = -65
(3) 3a - 2b = 2

Multiply (1) by -3, multiply (3) by 2, and add: Code:

-3(1) -6a + 15c = 54
2(3) 6a - 4b = 4
- - - - - - - - - - -
(4) - 4b + 15c = 58

Multiply (4) by 7, multiply (2) by 4, and add: Code:

7(4) -28b + 105c = 406
4(2) 28b - 32c = -260
- - - - - - - - - -
73c = 146

And we have: .c = 2

Substitute into (1): . 2a - 5·2 .= .-18 . → . a = -4

Substitute into (2): . 7b - 8·2 .= .-65 . → . b = -7

Therefore: .(a,b,c) .= .(-4,-7,2)